Investigation of bacterial neuraminidase inhibition of xanthones bearing geranyl and prenyl groups from Cratoxylum cochinchinense - Kim, Jeong Yoon; Li, Zuo Peng; Lee, Gihwan; Kim, Jeong Ho; Shah, Abdul Bari; Lee, Yong Hyun; Park, Ki Hun (Frontiers in Chemistry, 2023)
A series of xanthones (1-6) appended prenyl and geranyl groups on the A-ring were isolated, and compounds 1-3 were shown to be new xanthones. The analogues within this series were highly inhibited with excellent affinity against bacterial neuraminidase (BNA). A subtle change in the prenyl or geranyl motif affected the inhibitory potency and behavior significantly. For example, the inhibitory potency and binding affinity resulting from the geranyl group on C4:xanthone 1 (IC50 = 0.38 µM, KA = 2.4434 × 10 5 L•mol -1 ) were 100-fold different from those of xanthone 3 (IC50 = 35.8 µM, KA = 0.0002 × 10 5 L•mol -1 ). The most potent compound 1 was identified as a competitive inhibitor which interacted with BNA under reversible slow-binding inhibition: Ki app = 0.1440 µM, k3 = 0.1410 µM -1 s -1 , and k4 = 0.0203 min -1 . The inhibitory potencies (IC50) were doubly confirmed by the binding affinities (KA). The molecular docking (MD) and molecular dynamics simulations (MDS) studies also provided the critical information regarding the role of the geranyl and prenyl groups against BNA inhibition.